The Correlation between Pre-service EFL Teachers’ Extroversion and English Speaking Skills - Heriyanti Tahang; Anthoneta Mirino; Taslim Taslim; Isnaeni Wahab; Sitti Aisyah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
This study examines the relationship between extroversion and speaking proficiency among 27 pre-service English teachers at Universitas Muhammadiyah Sorong. Using a correlational research design, data were collected through the Revised-Short Form Eysenck Personality Questionnaire (EPQR-S) and a speaking skills test using a rubric by O'Malley (1996). The data were analysed using SPSS version 27 and Pearson product-moment correlation techniques. The results reveal an insignificant negative correlation (r = -0.108, p > 0.05) between extroversion and speaking skills, indicating no substantial link between these variables. Most students displayed moderate extroversion, but their speaking scores predominantly fell into the "enough" and "poor" categories. Highly extroverted students could have consistently achieved better speaking proficiency. Personalized teaching strategies are recommended to address students' diverse needs. Extroverted learners benefit from group discussions and collaborative projects, while introverted students perform better in quieter settings, such as one-on-one discussions or recorded tasks. These tailored approaches can enhance confidence and improve speaking skills across personality types. Further research is needed to explore other factors influencing pre-service teachers’ speaking skills.